KOMPETENSI PENGETAHUAN PEMBINA GERAKAN KELUARGA SAKINAH - Iwan Falahudin (Balai Diklat Keagamaan Jakarta, 2020)
This study aims to determine the differences in knowledge competencies of the participants of the Diklat Pembina Keluarga Sakinah before and after learning. The research was conducted at BDK Jakarta on Monday - Saturday, 11-16 November 2019. This research approach is quantitative with the ex post facto method. Data were collected through pre-test and post-test using multiple choice questions. The study population was the participants of three classes training totaling 120 participants. The data were processed using descriptive statistics by comparing the pre-test and post-test scores. The results showed that there had been a significant increase in the knowledge competence of the training participants. It is recommended that the relevant training should be continued with a larger number of generations.